Developing nursing approaches across the chronic illness trajectory: a grounded theory study of care from diagnosis to end-of-life in Western Amhara, Ethiopia - Abebe Dilie Afenigus; Mastewal Ayehu Sinshaw (Frontiers in Health Services)
BackgroundManaging chronic illness requires navigating a complex trajectory from diagnosis to end-of-life, with each phase necessitating specific nursing approaches. Effective management throughout these phases is vital for improving patient outcomes and quality of life.ObjectiveThis study aims to explore nursing approaches in managing chronic illness across its trajectory, from diagnosis to end-of-life care, focusing on phase-specific care, emotional support, education, interdisciplinary collaboration, and the challenges faced by nurses.MethodsA qualitative research design using a grounded theory approach was employed to construct a theoretical framework grounded with the insights and experience of nurses’ approaches across the chronic illness trajectory within Western Amhara, Ethiopia. The study comprised 24 nurses who were selected through the process of purposeful and theoretical sampling methods. Data was collected via in-depth interviews. Data analysis followed a constant comparative method, involving open, axial, and selective coding to identify key strategies and challenges across the illness trajectory.ResultsThe primary finding of this study emphasizes the evolving and adaptive role of nurses in chronic illness management, highlighting their ability to provide personalized care, emotional support, and education throughout the illness trajectory. Central to the investigation is the theory of nurses' evolving and adaptive role in chronic illness management, where they adjust their strategies to address the physical, emotional, and psychological needs of patients and families, from pre-diagnosis to end-of-life care. The study identifies key adaptive strategies, including fostering resilience, facilitating interdisciplinary collaboration, and managing fluctuating symptoms. Despite challenges such as heavy workloads and emotional strain, nurses require training for continuous professional development, technological integration, and collaborative platforms to reinforce their critical role in optimizing patient outcomes in chronic illness management.ConclusionThis study highlights nurses' adaptive role in chronic illness care, focusing on phase-specific interventions, emotional support, interdisciplinary collaboration, and education across entire illness trajectory to meet diverse needs of patients and their families. Despite challenges such as heavy workloads and emotional strain, the study recommends ongoing professional development and technological integration to optimize patient outcomes.